Coyuntura Económica - Aponte Jaramillo, Elizabeth; Sánchez Rengifo, Holmes; Vázquez Olave, Martha; Martínez Sandoval, Avelino; Carrillo-Rodríguez, Lilian Andrea; Ángel Giraldo, Leidy (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2006)
Coyuntura económica